Pengembangan Aplikasi Jual Beli Sayur di Kabupaten Malang (Studi Kasus : Desa Bocek Kabupaten Malang) - Rahma Kurniasari; Adam Hendra Brata; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The market chain is very detrimental to farmers as it creates a significant selling price gap between farmers and consumers. This problem occurs due to the market chain being very long, starting from farmers, collectors, middlemen, wholesalers, and finally, consumers. Therefore, a system is made to shorten the market chain so that farmers can get maximum profit. For this reason, it is necessary to design a web-based vegetable trading application using the SDLC Waterfall model method with the Sms-Gateway Platform. The results of this study aim to help farmers sell products directly to consumers without having to go through a long market chain in order for them to maximize profit.